New dynamics between China and Japan in Asia : how to build the future from the past? - Faure, Guy (World Scientific, 2010)
This book is a study of ties between China and Japan and their Asian counterparts. It does not therefore directly treat bilateral relations between these powers, as these already constitute the subject of many other studies. A lengthy perspective has been taken into account in order to recall past legacies, some of which are still painfully contentious, and to record evolutions in attitudes and strategies vis-a-vis Asian countries.